2008
DOI: 10.1007/s00420-008-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Major histopathological patterns of lung cancer related to arsenic exposure in German uranium miners

Abstract: These results indicate a cell type characteristic effect of arsenic in the development of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Arsenic, a known human carcinogen [49], was recently shown to increase lung cancer among uranium miners [50]; however, its contribution would probably be much smaller that RDP exposure. Importantly, measurement errors in exposure could have contributed to uncertainties in risk estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic, a known human carcinogen [49], was recently shown to increase lung cancer among uranium miners [50]; however, its contribution would probably be much smaller that RDP exposure. Importantly, measurement errors in exposure could have contributed to uncertainties in risk estimation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen and Chen (2002) found that Chinese tin miners with silicosis who were exposed to arsenic at three mines had an increased risk of lung cancer, but not at a fourth mine where arsenic concentrations were lower. In a study of inhaled arsenic, Taeger et al (2009) found that silicosis appeared to be related to the cell type of lung cancer among the uranium workers who were exposed to arsenic. However, it is difficult to draw conclusions from these studies because the mechanism of arsenic-related lung diseases and lung cancer may differ when arsenic is inhaled rather than ingested.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure of humans to arsenite and arsenite containing compounds is strongly associated with a myriad of health effects including increased incidence of tumors of the bladder, skin, and lung [210]. In addition to its carcinogenic effect, epidemiological studies have also associated chronic arsenite exposure with an increased risk in many human nonmalignant diseases, such as cardiovascular and peripheral vascular disease [11], chronic lung disease [12, 13], developmental anomalies [14, 15], and hematological disorder [16, 17]. …”
Section: Introductionmentioning
confidence: 99%